A tragédia moderna e a dialética da eticidade: o antagonismo dramático entre blanche dubois e Stanley Kowalski em um bonde chamado desejo - Araújo , João Doía de (2016)
The research developed in this study intends to analyze, in the light of the theory of social drama, the dramatic actions of the characters Blanche Dubois and Stanley Kowalski in Tennessee Williams’ play A Streetcar Named Desire (translated into Portuguese as Um Bonde Chamado Desejo). In the analysis of that dramatic text, we use, as a theoretical basis for this study, basic concepts related to the dramatic genre, taking as a starting point the fundamentals of Aristotelian tragedy, as well as the contributions of the analytical theory of modern drama formulated by authors such as Hegel, John Howard Lawson, Raymond Williams and Sandra Luna. The contributions of these theorists led us to discern conflictive events in the development of the plot, conflicts mainly engendered by the actions of the main characters: Blanche DuBois and Stanley Kowalski. The antagonism represented by these opponents reveals a dialectical interplay between each character’s ethos and their deeds and words. From the conflicts they experience in the plot, the dramatic actions become tragic, in the sense formulated by Raymond Williams who defines social drama as “modern tragedy”. This study does not intend to make an exhaustive investigation about the play, but to contribute to the debate on the proposal made in this research, opening further discussions regarding the dramatic action in the play.